Perbandingan Antara Peraturan Komisi Pemilihan Umum dan Qonun Aceh Dalam Mengatur Syarat Menjadi Anggota Legislatif - Rahmaniar Rahmaniar; M. Tamudin; Gibtiah Gibtiah (Muqaranah, 2022)
There are many things that must be fulfilled by members of the legislature, bearing in mind that the task of a representative of the people is not only to represent the people but he must be able to act wisely, fairly, and be able to carry out his duties according to the duties and functions of the members of the legislature itself. Therefore, this research will conduct a review of the requirements for candidates for legislative members in the General Election Commission Regulation (PKPU) No. 20 of 2018 and Aceh Qanun No. 3 of 2008. The purpose of this research is to examine the comparison between PKPU No. 20 of 2018 and Aceh Qanun No. 3 of 2008 in regulating the requirements for candidates for members of the legislature. The type of research used in this study is a type of normative legal research using library research. A comparative approach is used to examine the comparison between the two rules. The results of the study concluded that PKPU is a regulation that is comprehensive, binding, and must be obeyed by all Indonesian citizens regardless of their knowledge and abilities in the field of religion. Meanwhile, the Aceh Qanun is a type of regulation that is binding and must be obeyed by all the people of Aceh. The Aceh Qanun views that having extensive religious knowledge and ability is the most important requirement for anyone who will become a representative of the people.